IDENTIFIKASI DAYA TARIK WISATA NON-PROFIT (STUDI KASUS PADA PRAYER GARDEN DEPOK JAWA BARAT) - Fransiska Fitriani; Dwi Agus Kristianto (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Prayer garden depok, it's a new tourist attraction set up in the west Java area. Standing since 2015, Prayer Garden depok presents a religious pilgrimage/tour. In a unique construction, like the one found in the bible, of Solomon's temple, and furnished with the presence of prayer Caves, prayer Rooms, prayer Gardens, and prayer Chambers. The entire facility in Prayer Garden Depok can be enjoyed by any visitor for free, no charge. This is interesting, since normally a tourist attraction manager would collect fees on any visitor, starting with parking costs, admission fees, dining facilities, lodges, and so on. Thus, an identification must be necessary to know for the management of non-profit tourist attraction, such as Prayer Garden Depok, so that it can be a reference to other tourist attraction regulators. As for this study writers use qualitative descriptive methods. The conclusion that even though non-profit was derived, the manager of Paver Garden Depok kept adequate facilities for visitors and did not reduce service levels. Visitors can experience a certain amount of satisfaction from visiting Prayer Garden Depok. It can be seen from the enthusiasm of the visitor who wants to return to Praver Garden Depok.Keywords: Prayer Garden Depok, Prayer, non-profit, attraction, West Java